THE EFFECT OF EMOTIONAL MARKETING ON DONATION INTENTION (STUDY ON ADVERTISING IN KITABISA.COM CROWDFUNDING MEDIA PLATFORM) - Muhammad Haqqi Hudan Maulana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to determine the effect that occurs in emotional marketing to donation intention. Emotional marketing in this study can be measured using several variables, namely through visual stimulus, an auditory stimulus, and message framing to respondents who have been seen to the kitabisa.com platform donation advertisement. This study uses explanatory research methods that intend to explain the position of the variables studied and the influence of one variable with another variable through the submission of hypotheses. The sample used amounted to 120 respondents with a purposive sampling technique with the characteristics of a 17-year-old sample and had seen them at least 1-time platform kitabisa.com. The research test tool using a validity test, reliability test, and the classic assumption test. Hypothesis testing in this study using the t-test and F test with the result that visual stimulus and message framing have a partial effect while auditory stimulus have no partial effect on donation intention. The three variables that form emotional marketing simultaneously influence donation intention. Keywords: emotional marketing, visual stimulus, auditory stimulus, message framing, donation intention